(untitled) (Journal of School Administration Research and Development, 2021)
Today’s school leaders need to prioritize the development of leadership capacity in classroom teachers. Leadership development commonly involves either teachers expressing an interest in leadership or school leaders finding talent in those teachers whom they believe have the capacity to grow into formal leadership roles. School leaders must be able to recognize teachers who overflow with terrific ideas and leadership potential and those who are less likely to self-identify as leadership candidates. However, as a school administrator desires to cultivate leadership capacity in teachers, he or she must devise a plan. To accomplish this task effectively, best practices and theory must be utilized. Therefore, this essay addresses the use of best practices as identified in the literature to promote a positive school climate, collaboration, motivation, reflective practice, and teacher leadership development.